Non-alcoholic fatty liver disease enhances the beneficial effect of renal denervation on gut microbiota aberrations in rats with heart failure - Fuyan Chen; Zhiqin Guo; Yufeng Chen; Shun Li; Pingan Chen (BMC Microbiology)
Abstract Background Renal denervation (RDN) contributes to improving cardiac function by ameliorating aberrations of the gut microbiota, and non-alcoholic fatty liver disease (NAFLD) is associated with gut microbiota dysbiosis and is critically involved in the development of heart failure (HF). It is unclear whether the beneficial effect of RDN on gut microbiota in HF can be affected by NAFLD and whether this effect changes with the severity of NAFLD. Methods HF Sprague Dawley rats induced by transverse aortic constriction were fed a high-fat-fructose diet and underwent RDN, and sequencing of 16S rRNA gene in fecal samples was detected. Results The dissimilarity coefficients and sample distances of the intestinal microbiome were elevated in HF rats with NAFLD. After RDN, HF rats with NAFLD had fewer bacteria harmful to cardiac function, such as Alphaproteobacteria, Bacteroidota and Prevotella-9, and more bacteria beneficial to HF, such as Monoglobaceae, Proteobacteria and Monoglobales, than HF rats without NAFLD (all p < 0.05). This tendency also existed but was much less significant when compared between HF rats with non-alcoholic steatohepatitis (NASH) and without NAFLD. Predictive functional profiling of microbial communities revealed that after RDN, the abundance of membrane transport, environmental and genetic information processing was significantly higher, and glycan biosynthesis and metabolism was significantly lower in HF rats with NAFLD than in those without NAFLD. Conclusion NAFLD could further enhance the beneficial role of RDN in mitigating gut microbiota aberrations in HF rats by increasing beneficial bacteria and decreasing bacteria harmful to cardiac function, but this effect was not apparent in NASH rats.